MUHAMMAD QURAISH SHIHAB DAN PERSPEKTIFNYA TENTANG KORUPSI - Rahman Batubara; Hasan Basri (Smart Education, 2026)
Abstract: This study examines the interpretation of al-Misbah and the Insight of the Qur'an by Muhammad Quraish Shihab with the aim of knowing his perspective on the verses on corruption in responding to major problems that continue to be a serious challenge in the life of the nation and state. To find out his perspective, a literature study (library research) is used to trace the interpretation of related verses by referring directly to related sources, especially the interpretation of al-Misbah and the Insight of the Qur'an by Muhammad Quraish Shihab which is the primary data and other sources as secondary data. There are at least 5 aspects discussed by Muhammad Quraish Shihab in his work al-Misbah and the Insight of the Qur'an: Definition, types, causes, impacts and efforts to eradicate it. From the various interpretations that Quraish describes, it can be understood that corruption is seen as a serious problem that violates the principles of sharia and morality and requires serious efforts to eradicate it. Keywords: Corruption, Tafsir al-Misbah dan Wawasan al-Qur’an Abstrak: Penelitian ini mengkaji tafsir al-Misbah dan Wawasan al-Qur’an Muhammad Quraish Shihab dengan tujuan mengetahui perspektifnya tentang ayat-ayat korupsi dalam merespon persoalan besar yang terus menjadi tantangan serius dalam kehidupan berbangsa dan bernegara tersebut. Untuk mengetahui bagaimana perspektifnya, kajian kepustakaan (library research) digunakan untuk menelusuri penafsiran ayat-ayat yang terkait dengan merujuk langsung pada sumber-sumber yang berkaitan, khususnya tafsir al-Misbah dan Wawasan al-Qur’an karya Muhammad Quraish Shihab yang menjadi data primer dan sumber lain sebagai data sekunder. Setidaknya ada 5 segi yang dibahas oleh Muhammad Quraish Shihab dalam karyanya al-Misbah dan Wawasan al-Qur’an: Definisi, jenis, penyebab, dampak serta upaya memberantasnya. Dari berbagai penafsiran yang Quraish uraikan dapat difahami bahwa korupsi dipandang sebagai masalah serius yang melanggar prinsip-prinsip syariah dan moralitas serta diperlukan upaya yang serius pula untuk memberantasnya. Kata Kunci: Korupsi, Tafsir al-Misbah dan Wawasan al-Qur’an